Makna dan Nilai Opo Mpole Ka Lima Mpulu Ngkau pada Upacara Perkawinan Adat Kulawi (Kajian Hermeneutika) - Yunidar, Yunidar; Harisa, Sitti; Ferdinand, Frans (Jurnal Kreatif Online, 2020)
This study aimed to examine the meaning, value and function of the â€œopo mpole ka lima mpulu ngkauâ€ at the Kulawi traditional ceremony in the study of hermeneutics. This research was a qualitative study using an interactive data analysis model. The data were collected using open interview techniques in depth. Based on the results of the research obtained, it can be concluded that in the traditional language "opo mpole ka lima mpulu ngkau" at the wedding ceremony there are: 1) emotive, denotative, connotative, cognitive and idiomatic meanings that describe the dowry value in a community group and free symbolic expressions and non-symbolic through hermeneutic studies, 2) ethical values (philosophy of values) and aesthetic/ cultural values as a form of respect or appreciation for ancestors, marriage institutions, and parents who give birth to and raise their daughters, 3) social, religious and educational functions. (1) Social function (life harmony), namely a social situation and situation to achieve a good and prosperous life in accordance with the status it holds, which does not conflict with regulatory values and cultural values within the community in a community value; (2) the function of religion, namely the importance of understanding, that everything that is done is accountable to the Creator and perfection can only be achieved in society, nation and country through passion and piety to God Almighty; and (3) the educational function, namely moral learning or human manners obtained from the learning process both formal, non-formal, informal, and from everyday life related to the order of community life as a customary community in the community environment, which is transformed through hermeneutic studies.